AGRICULTURAL PRODUCTIVITY IN SUB-SAHARAN AFRICA: EFFECTS ON PRODUCTION AND FOOD PRICE VOLATILITY - (:unkn) unknown (My University, 2023)
This master's thesis analyzes the effects of agricultural productivity on food production and food price volatility in Sub-Saharan Africa. To achieve this goal, it uses a sample of 11 and 14 Sub-Saharan African countries, and employs FMOLS, DOLS, and PMG estimation techniques. The results indicate that agricultural productivity, measured by the index of Agricultural Total Factor Productivity (ATFP) has a significant effect on food production and food price volatility in Sub-Saharan Africa. These results confirm the causal relationship between these variables. The study's findings highlight various associations between economic and agricultural variables, with significant political implications. Increasing agricultural productivity increases food production June 14, 2023 – Page 2/3 but also raises food price volatility. Economic growth can either stimulate or reduce food production, depending on the specifications used. Climate change reduces food production. Foreign Direct Investment (FDI) can also negatively impact food production. These findings underscore the importance of adopting thoughtful public policies to ensure stable food production. Policies that promote agricultural productivity investments can improve food security while stimulating economic growth. Governments should also invest in initiatives that reduce the negative effects of climate change, such as sustainable farming practices. Additionally, policies that encourage local food production and consumption can reduce foreign investment dependence and help lower food price volatility. The findings also stress the need for context-specific policy decision-making, as the effects of economic and agricultural variables vary depending on the economic models' specifications used.
Keywords: African Research